Cost Optimization Through Quality Management for a Sustainable IT Company - Till, József; Késmárki-Gally, Szilvia Erdeiné; Vágány, Judit Bernadett (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Numerous studies support the notion that quality management plays a crucial role in enhancing economic efficiency, particularly through cost reduction and the optimization of operational processes. Companies operating in the IT sector typically focus on compliance with the ISO 27001 and ISO 20000 management systems. Additionally, in recent years, the emergence of frameworks such as NIS 2, DORA, and ESG has introduced new challenges for industry stakeholders. It is also essential to mention ITIL, which serves as the repository of “best practices,” as the proper implementation of this system significantly influences the efficiency and quality of IT services. The aim of this publication is to compare and examine the requirements of the standards and frameworks, assessing their impact on cost reduction and efficiency improvement in quality management, as well as their effects on the sustainability of management systems. The risks and opportunities associated with these frameworks are analyzed using secondary research, answering my research questions through the review of relevant academic literature. The expected findings of this research suggest that integrating these new regulations and frameworks into corporate strategy not only facilitates legal compliance but also contributes to cost reduction and process efficiency improvement in the long term.